Under the blood-red sun - Salisbury, Graham. (Delacorte Press, 1994)
Tomikazu Nakaji's biggest concerns are baseball, homework, and a local bully, until life with his Japanese family in Hawaii changes drastically after the bombing of Pearl Harbor in December 1941.